Intermittent attendance at breast cancer screening - Padraic Fleming; Sinead O'Neill; Miriam Owens; Therese Mooney; Patricia Fitzpatrick (SAGE Publishing, 2013)
Background. To determine why women skip rounds and factors influencing return of previous non attenders (PNAs) to breast screening. Design and methods. Retrospective, quantitative, structured questionnaire posted to 2500 women. First PNAs did not attend their first screening appointment in 2007/2008 but then attended in 2010; First Controls first attended in 2010 without missed previous appointments. Women who attended screening in 2006 or earlier then skipped a round but returned in 2010 were Subsequent PNAs; Subsequent Controls attended all appointments. Results. More First Controls than First PNAs had family history of cancer (72.7% vs 63.2%; P=0.003); breast cancer (31.3% vs 24.8%; P=0.04). More PNAs lived rurally; more First PNAs had 3rd level education (33.2% vs 23.6%; P=0.002) and fewer had private insurance than First Controls (57.7% vs 64.8%; P=0.04). Excellent/good health was reported in First PNAs and First Controls (82.9% vs 83.2%), but fewer Subsequent PNAs than Subsequent Controls (72.7% vs 84.9%; P=0.000). Common considerations at time of missed appointment were had mammogram elsewhere (33% First PNA) and postponed to next round (16% First PNA, 18.8% Subsequent PNA). Considerations when returning to screening were similar for First PNAs and Subsequent PNAs: I am older (35.4%, 29.6%), I made sure I remembered (29%, 23.6%), could reschedule (17.6%, 20.6%), illness of more concern (16.5%, 19%). More First PNAs stated my family/friends advised (22.3% vs 15.2%) or my GP (12.6% vs 4.6%) advised me to attend, heard good things about BreastCheck (28.8% vs 13.6%). Conclusions. Intermittent attenders do not fit socio-demographic patterns of non-attenders; GP recommendation and word of mouth were important in women's return to screening. Fear and anxiety seem to act as a screening facilitator rather than an inhibitor.